Ekstraksi Antioksidan Alami Dan Uji Aktifitas Antioksidan Dari Daun Sirsak (Annona muricata L.) - Addin Akbar; Rita Youfa (REACTOR: Journal of Research on Chemistry and Engineering, 2020)
Antioxidant extracted from soursop leaves with solvent extraction and stirring methods. Ethanol, ethyl acetate, and n-hexane use as a solvent. Extraction temperature varied of 35 °, 45 °, 55 ° C. The highest yield obtained was 20.2% from the ethanol extraction at a temperature of 55 °C. Test result of antioxidant activity using DPPH method indicates that the ethyl acetate fraction has the highest activity with% RSA 81.10 followed by ethanol and nhexane fraction of 69.64% and 27.60%. GCMS analysis indicated that the ethyl acetate fraction has the most antioxidant compounds with 11 compounds followed by ethanol fraction and n-hexane which has 9 and 4 antioxidant compounds with the highest content is the tocopherol group.